Contributions from the web to the citizen participation and democratic representation - Aguirre, Jorge (Revista Chilena de Derecho y Tecnología, 2015)
From the restlessness of the communicative and deliberative quality of democracy, the objective is to analyze Web’s contributions to political representation and citizen participation; contrasting the traditional mass media with Information and Communication Technologies and distinguishes forms of participation, differentiate with the activism. The premises are established: e-democracy, e-government, governance and open government; to compare the governability of governance and the different models of e-government. Consistent object of study: the quality of democracy, the method qualitative conceptualized Web’s contributions to political representation and citizen participation. The former include suggestions for political representatives elected office and the latter are exemplified by successful cases worldwide. Finally, it shows general data on the Mexican e-government and concluding discussions that may inspire new recommendations.